Александр Сергеевич Пушкин - Самарцев Александр Давидович (История России, 2010)
Экземпляры: (20110141) / Инвентарный номер: 47301 / Цена: 173.52 / Сис.шифр: 83.3(2Рос=Рус)1ср. / Авт.знак: С 17 / ББК: 83.3(2Рос=Рус)1ср.